The impact and pattern of WhatsApp use among the school students during the COVID-19 lockdown in a city of Western India: a cross-sectional study - Engti, Raktim; Momin, Mohmmedirfan H.; Vyas, Shailee N. (International Journal Of Community Medicine And Public Health, 2023)
Background: COVID-19 pandemic has been a global serious problem adversely affecting human life. This study aimed at documenting the impact and pattern of WhatsApp use among the school students during these unprecedented times. Methods: A cross-sectional study was conducted on 434 students belonging to grade IX, X, XI and XII, of 13-19years age group, from randomly selected four English medium schools of Surat city, India. Univariate and bivariate analysis was carried out by Epi-info software. Results: One out of every six students (16.5%) of Class IX used WhatsApp for >1 hour per day compared to 13.6% of Class XII students (χ2: 23.478, DF=6, p=0.001). The total time spent on WhatsApp per day by 22.8% of girls and 13.5% of boys was >1 hour (χ2: 11.532, DF=2, p=0.003). Almost 22% students of Class IX were checking WhatsApp status every time they hear message tone compared to 15.2% of Class XII students at work/ class (χ2: 19.168, DF=9, p=0.024) and at home/leisure time (χ2: 19.009, DF=9, p=0.025). A quarter (23.04%) of students reported that they would continue the use of WhatsApp even if it becomes a paid application. The most common reason for using WhatsApp among boys was its user-friendly nature while for the girls it was the ease of use. Conclusions: Girls as compared to boys spend more time on WhatsApp per day and have more number of groups where they are active. Class IX students were more prone for problematic use of WhatsApp as compared to the rest.